Changes in driving patterns of older Australians: Findings from the Candrive/Ozcandrive cohort study. (November 2019) - Charlton, J.L.; Koppel, S.; D'Elia, A.; Hua, P.; St. Louis, R.; Darzins, P.; Di Stefano, M.; Odell, M.; Porter, M.; Myers, A.; Tuokko, H.; Marshall, S.
Highlights: Insights on real-world driving patterns, health and functional changes of older drivers. Reduced annual distance was associated with being female, increasing age, and health drop-out status. Reduced annual trip frequency was associated with age and health drop-out status. Results suggest self-regulation and may reflect adaptation to health or functional changes. Abstract: This paper describes changes in driving patterns over a five-year period of drivers aged 75 years and older (Year 1: Male = 68.9%; Age = M = 79.5 years, SD = 3.4 years, Range: 75.0–88.0 years) in the Candrive/Ozcandrive cohort study. Participants completed various functional and health assessments and self-reported driving questionnaires. In-vehicle data-loggers, installed in participants' own vehicles, also monitored spatio-temporal characteristics of participants' everyday driving trips. Data for a subset of one hundred and ninety-one Ozcandrive participants from Melbourne, Australia were analysed. Reductions in driving trip distance and frequency were observed over the five years. On average, in Year 1, participants drove 1223 (SD = 502) trips, totalling 8993 (SD = 5169) kilometers annually, decreasing significantly to 1028 trips (SD = 559) trips and 6787 (SD = 4624) kilometers in Year 5. On average, in Year 1, participants' driving trips were around 7.5 km (SD = 3.2), decreasing in distance significantly to 6.9 km (SD 3.9) in Year 5. Log-normal General Estimating Equation (GEE) modelling was conducted for selected driving exposure measures (annual distance driven, annual trip frequency, trip distance, etc.). Reductions in overall annual distance driven were significantly associated with being female, increasing age, withdrawal from the study for health reasons and lower night-time driving comfort scores (marginally significant). Reductions in annual trip frequency were associated with increasing age and withdrawal from the study for health reasons. Results suggest drivers practiced self-regulation, which may reflect adaption to deterioration in health and functional status.